Ultraviolet photovoltaic effect in BiFeO3/Nb-SrTiO3 heterostructure - Li, H. (2013)
We report on ultraviolet photovoltaic effects in a BiFeO3/Nb-doped SrTiO3 heterostructure prepared by a pulsed laser deposition method. The heterostructure exhibits rectifying behaviors in the temperature range from 80 K to 300 K. The photovoltage of heterostructure is about 0.33 V at T = 80 K when it is illuminated by a KrF excimer laser with a wavelength of 248 nm. The peak photovoltages decrease with increasing the temperature because of the accumulation of photogenerated carriers. Moreover, the peak photovoltages of heterostructure almost linearly increase with an increase of the power density of laser at T = 300 K. The results reveal some properties that may be useful for possible applications in multiferroic photoelectric devices.